THE TRANSLATION ACCEPTABILITY OF COMPLAIN RESPONDING TURN IN SHOPAHOLIC TO THE RESCUE - Setia Adi Nugraha; Mangatur Nababan; Djatmika Djatmika (Indonesian EFL Journal, 2019)
The purpose of this research was to know the translations techniques, the accuracy as well as the acceptability of the translations. It was a descriptive-qualitative research with an embedded case study by using pragmatics approach. This research was done by listing the conversations between characters in the Shopaholic to the Rescue novel which contains turns that respond to complaining speech act. Here, the source language and target language were compared to identify the translation techniques. Then, the researcher and the raters assessed the acceptability of the translations by conducting Focus Group Discussion (FGD). The result showed that there are 14 techniques used by the translator, such as established equivalent, variation, pure borrowing, modulation, explicitation, implicitation, addition, transposition, reduction, linguistic compression, literal, generalization, discursive creation, and linguistic amplification. Moreover, the average rate of the acceptability is 2.94 out of 3 which means it is prevalent, in line with the norm as well as the rule of the target language.